Papéis de marketing em um sistema de capital de distribuição: estudos de casos sobre diferentes composições organizacionais - Nogueira, José Francisco (2003)
The purpose of this work is to identify the inforrnation technology (IT) component distribution channel marketing roles, emphasizing this observation on market oriented organization activities to enhancement the relation with corporate customer, and correct positioning of wich component channel brand, whatever brand and technology represented by these companies. To maintain better homogeneity of this evaluation, this study focused all observation on components channel cases that has established on Brazilian country that represented by same brand and manufacturer. The researches comparues have different sizes, In terrn of annual amount sales and dimensions of market share, as quantity and geographic customer dispersion. The observations indicated that few marketing roles and activities are commons to researched cases. Besides, the study also indicated that basic marketing roles set to ideal customer reIatíonsrup aIthough contaíned on system chaín, ís not strategíc organízed. AIso as oóserved that eventually there are useless of some roles or superposition of others.